2019
DOI: 10.1021/acs.chemrestox.9b00179
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Stone Wool Fibers with Phenol-urea-formaldehyde Binder in a Synthetic Lung Fluid

Abstract: Mineral wool products, composed of stone wool fibers and organic binder, are used in many construction applications. Among all their beneficial properties, the most important requirement is safety for human health, such as when fibers are inhaled. For determining long-term toxicity, biosolubility and biopersistence studies in vitro and in vivo are essential. In vitro fiber dissolution rate, which depends on the medium, fiber composition, and the surface available for dissolution, is a key parameter in determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 67 publications
8
32
1
Order By: Relevance
“…a robust dissolution test but should simulate physiological conditions. The near-complete coating by the binder is one of the relevant factors, 9,19 and is supported by the re-analysis of MMVF surfaces by XPS aer dissolution testing: Barly et al found that, aer dissolution testing, the surfaces assimilated from any initial content of binder to a C/Si ratio of 7-10 (compared to a value (1 measured on the MMVF without binder), 8 which we interpret as indication of a universal organic-inorganic composite gel formation that is triggered by the binder, but is not directly scaling with binder content, consistent with our ndings.…”
Section: Correlation With Dissolution Ratesmentioning
confidence: 96%
“…a robust dissolution test but should simulate physiological conditions. The near-complete coating by the binder is one of the relevant factors, 9,19 and is supported by the re-analysis of MMVF surfaces by XPS aer dissolution testing: Barly et al found that, aer dissolution testing, the surfaces assimilated from any initial content of binder to a C/Si ratio of 7-10 (compared to a value (1 measured on the MMVF without binder), 8 which we interpret as indication of a universal organic-inorganic composite gel formation that is triggered by the binder, but is not directly scaling with binder content, consistent with our ndings.…”
Section: Correlation With Dissolution Ratesmentioning
confidence: 96%
“…In this study, the chemical composition of GFW is an aluminosilicate glass system, similar to Ca-Mg aluminosilicate stone wool fiber, but with less alkali content. Its surface layer has significant dissolution rates with sodium-based lung fluid and preferential leaching of matrix at the low pH of 4.5 [29]. Therefore, this study proposed transforming a valuable waste from the glass fibers into mesoporous zeolite-like nanomaterial (MZN) to adsorb methylene blue in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Many other examples of this phenomenon can be found in the literature (Hedberg et al 2010;Rozalen et al 2013;Boisa et al 2014;Utembe et al 2015;Barly et al 2019;Zhong et al 2019). In fact, an excellent correlation was shown between ALF and a sodium citrate buffer, suggesting that no other components of ALF contribute significantly to the extraction efficiency (Mukhtar et al 2015).…”
Section: Citrate Oxalate Tartrate and Edtamentioning
confidence: 84%
“…MgHCit and MgH 2 Cit þ ) form, peaking at pH 3-4 and falling by pH 6 (Rozalen et al 2013). Barly et al (2019) also attributed high stone wool fibre dissolution in acidic-modified Gamble's solution to the complexation effects of citrate and tartrate, namely on Fe and Al, and determined that dissolution rates were significantly faster than in solutions of similar pH where no complexing agents were present. Likewise, Steenberg et al (2001) found that citric acid greatly increased dissolution of stone wool fibres, which was not observed with the addition of acetic acid.…”
Section: Citrate Oxalate Tartrate and Edtamentioning
confidence: 96%
See 1 more Smart Citation